2020
DOI: 10.1186/s12955-020-01374-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality of nurses in the emergency department of public hospitals in China and its influencing factors: a cross-sectional study

Abstract: Background: Studies have shown that poor sleep could result in many unpleasant consequences and is prevalent in nurses. Considering the fact of high stress, overwhelming workload and many night shifts in the emergency department in China, this study aimed to evaluate the current status of emergency nurses' sleep quality in public hospitals in Shandong, China and explored its influencing factors. Methods: A self-administered questionnaire incorporating the Job Content Questionnaire and Pittsburgh Sleep Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 54 publications
(69 reference statements)
8
37
0
7
Order By: Relevance
“…In relation to income, most of the professionals reported earning from three to five minimum wages, having only one job and working up to 40 hours during the week, which is similar to a research study carried out in the North of Paraná (Brazil), in which professionals had only one job (56.7%) and earned from one to two minimum wages ( 7 ) . Likewise, another study developed in China, with nurses working in different hospital units, presented 4,185 female professionals, with only one job and who worked up to 45 weekly hours ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In relation to income, most of the professionals reported earning from three to five minimum wages, having only one job and working up to 40 hours during the week, which is similar to a research study carried out in the North of Paraná (Brazil), in which professionals had only one job (56.7%) and earned from one to two minimum wages ( 7 ) . Likewise, another study developed in China, with nurses working in different hospital units, presented 4,185 female professionals, with only one job and who worked up to 45 weekly hours ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in hospital units in Iran obtained 77.4% (418) of the nurses considered as with poor sleep ( 11 ) . Another study, developed in China with 4,730 nurses working in emergency units, found 65.8% of the professionals with altered sleep ( 21 ) . This finding is similar to the study conducted in India, which obtained 83.2% of the nurses as with poor sleep ( 10 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that nurses routinely suffer alterations in sleep quality, not only due to work schedules, also because of psychological stress [ 24 , 25 , 26 ]. Sleeping few hours per day for a prolonged period of time is associated with an alteration of the brain mechanism and its function in the emotional field, resulting in a more negative mood (behavioral impairment) [ 11 , 27 , 28 , 29 ]. Lack of sleep has been found to impair abilities that have a specific role in EI and may affect emotion processing [ 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%